Determining the Best Sectioning Method and Intestinal Segment for Morphometric Analysis in Broilers - MS Gava; LB Moraes; D Carvalho; GZ Chitolina; LCB Fallavena; HLS Moraes; J Herpich; CTP Salle (Brazilian Journal of Poultry Science, 2015)
Brazilian poultry production is very efficient and demands maximum broiler performance. Therefore, digestive system pathologies have a relevant role. Considering it is difficult to obtain consistent information on intestinal morphometric analysis, this study aimed at establishing essential and clear criteria for the collection of intestinal segments for morphometric analysis. Fifteen 13-d-old broilers were sacrificed and three intestinal segments were collected per bird. Two 3-cm long sections were obtained from each of the intestinal segments. Samples were collected open or closed. The closed samples were transversely, hemicylindrically, or longitudinally sectioned. Samples were processed and stained with hematoxylin and eosin. The number of microscopic fields in each section was counted. Villi presenting the base clearly embedded in the submucosa, no damage or folds, and simple columnar epithelium at the tip were considered adequate for measurements. These villi were counted in each sample. The results shows that hemicylindrical sections presented the highest number of observation fields, with an average of 9.76 fields. Jejunum samples were among the three highest average villi counts, with 18.23 in longitudinal sections and 15.61 in hemicylindrical sections. The results of the present study indicate that hemicylindrical sectioning and jejunal samples were, respectively, the best sectioning method and the best intestinal segment for the morphometric analysis of the intestines of broilers.